Intra‐hippocampal injections of Aβ oligomers induce cognitive impairments associated with neurodegeneration and activation of microglia in senescent mice: Characterization of a novel animal model of Alzheimer's disease. (December 2021) - Henriques, Alexandre; Jégo, Pierrick; Farrugia, Clémence; Callizot, Noelle
Abstract: Background: Alzheimer's disease is characterized by the extracellular accumulation of senile plaques composed of amyloid beta and the intracellular deposition of neurofibrillary tangles composed of hyperphosphorylated tau. Aβ oligomers (AβO)‐induced neurotoxicity is characterized by sequential loss of synapses, followed by axonal damage and neuronal death. AβO induce also a phenotypic shift from resident to activated M1‐microglial cells, which directly contribute to neuronal loss. Here, we aimed to characterize the toxicity of AβO in a novel in vivo model of Alzheimer's disease. Method: Mice at 18‐month of age were bilaterally injected with a solution of Aβ1‐42 (100 µM) containing oligomers (15% precisely determined by automated protein analysis). Short‐ and long‐term spatial memories were evaluated several days after injury in the Y‐maze and in the Morris water maze test. The brain were dissected for immunohisto‐analysis. Result: AβO‐injected mice displayed clear deficit in spatial memory. They explored less the new arm in the forced‐alteration Y‐maze test, when compared to control mice. In addition, AβO‐injected mice presented with deficit in learning and memory retention in the Morris water maze test. Cognitive functions were restored after administration of donepezil. Neurodegenerative processes, (neuron and synapses loss), were evidenced by immunostaining in CA1 area of the hippocampus. Neuronal loss was associated with a large activation of microglial cells. Conclusion: Altogether, intra‐hippocampal injections of AβO led to behavioural and histologic phenotypes highly similar to pathological hallmarks of Alzheimer's disease. This new animal model of Alzheimer's disease represents a valuable tool for studying the toxicity of AβO and evaluating protective effects of drug candidates.